Client-related factors affecting delays in Malaysian school construction projects - Najuwa, Mohd Nasir (2018)
Construction industry is an important sector which helps in developing the economic growth of Malaysia but many construction projects are prone to delay. Although many studies have been made on delay factors in generally towards Malaysian construction project, there is still lack of study about client related factors specifically which bring into delay of the project. The main purpose of this study is to identifying the client related factors toward delay in school construction projects located in Pulau Pinang, Kedah and Perlis. This study takes a qualitative approach to gain information from three case studies selected. Data is collected by interviewing six project participants consists of contractors and consultants with working experience ranging from 15 to 26 years. This study identified six major categories of client related factors were mismanagement at early planning, improper hiring process, poor of knowledge, delay in payment, lack of project monitoring, and lack of preparation on required document. Hence, five significant impacts were found: negative social impact towards work environment, design changes during construction phase, dispute between client, contractor and consultant, dependency of contractor towards client financial support, and poor of performance in project progress. This study has indicate seven recommendations for client which were good understanding toward cause and effect of delay, improve awareness on soft skills, adequate acknowledge and experience, good participation and commitment to team work, consider background details and experience for team selection, more spaces for designers in detailing and preparing the design and BIM (Building Information Modeling) should be introduced at early stage of institution. This study contributes a value added for future research in area of client related factors and helps to improve client capability towards project success in time completion.